Improving Integrity in Research and Higher Education: An Indonesian Perspective: [Meningkatkan Integritas Dalam Riset dan Pendidikan Tinggi: Sebuah Perspektif Indonesia] - Kozok, Uli; Siaputra, Ide Bagus (Faculty of Psychology, Universitas Surabaya, 2023)
Students and lecturers have challenges in publishing the results of their researches and studies as a requirement for graduation, promotion, or performance evaluation for institutions. This can bring up a variety of behaviors in producing scientific papers, ranging from those that should be emulated, questioned, doubtful, to being considered violations. The Indonesian government has issued regulations on academic integrity in producing scientific papers, but there are still new challenges such as misinformation and the use of artificial intelligence. Therefore, there is a need for indicators received together about the level of reasonableness in producing scientific work. This indicator must be relevant globally and accommodative to the local context. To strive for this, it is important to strive for dialogue between the academic community and the government to review publication policies and ensure that the regulations are effective and adaptive to the times and technological progress. Mahasiswa dan dosen memiliki tantangan dalam mempublikasikan hasil penelitian dan studi mereka sebagai syarat kelulusan, kenaikan jabatan, atau evaluasi kinerja bagi lembaga. Hal ini dapat memunculkan beragam perilaku dalam menghasilkan karya ilmiah, mulai dari yang patut dicontoh, dipertanyakan, meragukan, hingga dianggap pelanggaran. Pemerintah Indonesia sudah menerbitkan peraturan tentang integritas akademik dalam menghasilkan karya ilmiah, namun masih ada tantangan baru seperti misinformasi dan penggunaan kecerdasan buatan. Maka dari itu, perlu ada indikator yang diterima bersama tentang tingkat kewajaran dalam menghasilkan karya ilmiah. Indikator ini harus relevan secara global dan akomodatif dengan konteks lokal. Untuk mengupayakan hal tersebut, penting untuk mengupayakan dialog antara sivitas akademika dan pemerintah untuk meninjau kembali kebijakan publikasi dan memastikan bahwa peraturan tersebut efektif dan adaptif terhadap perkembangan zaman dan kemajuan teknologi.